2010
DOI: 10.1002/ibd.21156
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Spanish version of a questionnaire to measure quality of care through the eyes of patients with inflammatory bowel disease (QUOTE-IBD)

Abstract: The Spanish QUOTE-IBD has proved to be a valid instrument to measure the quality of health care for patients with CD and UC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 14 publications
2
15
0
2
Order By: Relevance
“…This is in agreement with previous results (Masachs et al . ) showing that information was the most important aspect of high‐quality care in terms of informing about examinations and possible physical problems unrelated to IBD in clear and understandable language (Masachs et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with previous results (Masachs et al . ) showing that information was the most important aspect of high‐quality care in terms of informing about examinations and possible physical problems unrelated to IBD in clear and understandable language (Masachs et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…, Masachs et al . ) revealed that persons with IBD reported suboptimal care in areas such as accommodation, accessibility and information, as well as psychological and physical well‐being. Also surgery, younger age and longer disease duration play an important role in the experience of the quality of care (van der Eijk et al .…”
Section: Introductionmentioning
confidence: 99%
“…In response to the application of visual analog scales specifically designed to assess user satisfaction with the UACC, the patients expressed a high degree of satisfaction (score 9/10) in reference to areas such as healthcare continuity, convenience, accessibility, courtesy and professional competence (8). The availability of a specialized continued and IBD patient-centered healthcare tool such as the UACC model improves patient care and satisfaction, though it remains to be established whether it is also accompanied by an excessive burden in terms of hospital resource utilization.…”
Section: Introductionmentioning
confidence: 99%
“…The existing knowledge about IBD and quality of care is based on studies measuring quality of care with predefined questions (86,88). Results from the QUOTE-IBD studies showed that the lowest importance scores were observed for autonomy, costs and accessibility.…”
Section: Assessing Quality Of Carementioning
confidence: 99%
“…Results from the QUOTE-IBD studies showed that the lowest importance scores were observed for autonomy, costs and accessibility. The three most important aspects of quality of care for IBD patients were competence, accommodation and courtesy (86,88). In the Portuguese version of the QUOTE-IBD, it was concluded that there is no golden standard for the assessment of quality of care from the perspective of those living with IBD.…”
Section: Assessing Quality Of Carementioning
confidence: 99%